The effect of resistance training in a hypoxic chamber on physical performance in elite rugby athletes - Mayo, B.; Miles, C.; Sims, S.; Driller, M. (High Altitude Medicine & Biology, 2018)
Limited research suggests that muscle adaptations may be enhanced through resistance training in a hypoxic environment. Seventeen professional rugby union athletes (age [mean±SD], 24±3 years; body mass, 98.7±12.8 kg; and height, 188.9±7.9 cm), performed 12 resistance training sessions over a 3-week period. Participants were randomly divided into two groups: HYP (n=8), where resistance training sessions were performed in an environmental chamber with O2 concentration maintained at ~14.4% (~3000 m simulated altitude), or CON (n=9), where identical resistance training sessions were performed without the simulated altitude (O2=20.9%, at sea level). Before and after the training intervention, tests included measures of strength, power, endurance, speed, and body composition. Two-way interactions between treatment and time for any of the measured variables were not significant (p>0.05). Small positive effect sizes for HYP were found for bench press (d=0.24), weighted chin-up (d=0.23), and bronco endurance tests (d=-0.21). Resistance training in a hypoxic environmental chamber may lead to small improvements in upper body strength and endurance compared to the same training performed at sea level. These findings are somewhat novel, given the short timeframe of the study and the elite population sampled.